2020
DOI: 10.5719/hgeo.2020.142.5
|View full text |Cite
|
Sign up to set email alerts
|

‘Work from home’ as an alternative to daily commuting for working women

Abstract: This study examines the viability of working from home as an alternative to daily commuting for the working women of the Mumbai Metropolitan Region in India. Work from home has become a common practice in India following the outbreak of the COVID-19 pandemic. In the mentioned area of India people are known to commute for long distances daily to reach their workplaces, and the ability to work from home has led to saving a lot of time that otherwise used to be lost in commuting. Despite this, the present study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…In another study, flexible working hours were perceived as a benefit of working from home and an increased focus on work was also reported ( Diab-Bahman and Al-Enzi, 2020 ). In contrast, in a study on women who worked from home in India ( Bhattacharjee, 2020 ), the participants reported that working from home had some disadvantages, such as difficulty transitioning between their domestic role and working role, and the added burden of chores.…”
Section: Resultsmentioning
confidence: 90%
“…In another study, flexible working hours were perceived as a benefit of working from home and an increased focus on work was also reported ( Diab-Bahman and Al-Enzi, 2020 ). In contrast, in a study on women who worked from home in India ( Bhattacharjee, 2020 ), the participants reported that working from home had some disadvantages, such as difficulty transitioning between their domestic role and working role, and the added burden of chores.…”
Section: Resultsmentioning
confidence: 90%
“…al., 2020;Meyer et. al., 2021;Bhattacharjee, 2020). This can also lead to burnout since they must balance work and family during that time (Feng & Savani, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…al., 2021;Yerkes et. al., 2020;Bhattacharjee, 2020). This pandemic also shows negative signs for employees as they experience more open stress from both work and personal life, which can cause disruption in their work-life balance (Marimuthu, 2020;Anwar et.…”
Section: Methodsmentioning
confidence: 99%
“…Mereka merasa menjalani pekerjaan tanpa beban karena tidak pernah lagi meninggalkan keluarga ke luar kota seperti sebelumnya dan semua pekerjaan dapat dilakukan di rumah sambil menjaga anak-anak dan keluarga. Senada dengan wanita pekerja di India, mereka melakukan perjalanan jarak jauh setiap hari untuk mencapai tempat kerja, dan kemampuan untuk bekerja dari rumah telah menghemat banyak waktu yang biasanya hilang dalam perjalanan, sehingga waktu tersebut lebih bermanfaat untuk menyeimbangkan peran yang lain (Bhattacharjee, 2020).…”
Section: Hasil Dan Pembahasanunclassified